2001
DOI: 10.1152/ajprenal.0139.2001
|View full text |Cite
|
Sign up to set email alerts
|

Food restriction prevents age-related polyuria by vasopressin-dependent recruitment of aquaporin-2

Abstract: The mechanisms underlying the prevention of age-related polyuria by chronic food restriction were investigated in female WAG/Rij rats. The decreased osmolality of renal papilla observed in senescent rats was not corrected by food restriction. A reduced urea content in the inner medulla of senescent rats, fed ad libitum or food-restricted, was suggested by the marked decrease in expression of UT-A1 and UT-B1 urea transporters. Aquaporin-2 (AQP2) downregulation in the inner medulla of senescent rats was partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 51 publications
3
29
1
Order By: Relevance
“…Both of these parameters are also strongly influenced by AVP through the V2R. In this regard, previous studies showed reduced AVP-dependent reabsorption of sodium by thick ascending limb of Henle's loop in senescent mice (14) and decreased medullary abundances of UT-A1 and UT-B1 urea transporters resulting in decreased papillary urea concentrations and osmolality in aged WAG/Rij rats (7,8,48). Thus each of these factors in addition to AQP2 expression may contribute to the observed changes in urinary concentration with aging, and further studies will be needed to assess the relative contributions of each of these factors under different physiological conditions in F344BN rats.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Both of these parameters are also strongly influenced by AVP through the V2R. In this regard, previous studies showed reduced AVP-dependent reabsorption of sodium by thick ascending limb of Henle's loop in senescent mice (14) and decreased medullary abundances of UT-A1 and UT-B1 urea transporters resulting in decreased papillary urea concentrations and osmolality in aged WAG/Rij rats (7,8,48). Thus each of these factors in addition to AQP2 expression may contribute to the observed changes in urinary concentration with aging, and further studies will be needed to assess the relative contributions of each of these factors under different physiological conditions in F344BN rats.…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, most studies are consistent with a reduced renal cellular response to AVP, leading to decreased water permeability of the collecting duct, as an important contributor to age-associated impairments in renal concentrating ability (5,6,19). Studies showing reduced AVPdependent reabsorption of sodium by the thick ascending limb of Henle's loop in senescent mice (14) and decreased expression of the AVP-stimulated urea transporter UT-A1 in aged female WAG/Rij rats (7,8,48) further support an altered renal responsiveness to AVP with aging.AVP plays a critical role in the regulation of renal water excretion. AVP increases water permeability in the collecting duct of the kidney by regulating membrane insertion and abundance of the water channel aquaporin-2 (AQP2).…”
mentioning
confidence: 86%
“…Some urea transporter expressions have been studied in the aging kidney of rats. Markedly reduced kidney UT-A1, UT-A2, and UT-B1 abundances have been reported in senescent rats (27,28). Moreover, a different regional expression for UT-B1 within the inner medulla has been disclosed in the course of aging.…”
Section: Discussionmentioning
confidence: 98%
“…AVP binds to the vasopressin 2 receptor (V2R) in the basolateral membrane of the collecting duct cells of the kidney and the eventual phosphorylation and translocation of aquaporin-2 (AQP-2) to the apical membrane increase the permeability of the collecting ducts to water, allowing for conservation of fluid (3). However, some ageing rat models reported impairment in urine-concentrating ability despite similar levels of AVP secretion, suggesting that the impairment is attributed to a de-crease in the renal expression of AQP-2 (7,41). Rats with chronic renal failure induced by a surgical reduction in renal mass have decreased urinary concentrating ability that is associated with a downregulation of AQP-2 as well (17).…”
mentioning
confidence: 99%